O czym rozprawiają matematycy, c zyli o statusie bytowym przedmiotów matematyki - Murawski, Roman (Wydawnictwo Naukowe UAM, 2004)
In this article the author considers various conceptions concerning ontological status of the objects of mathematics. The relation is show between these problems and a dispute over universals, and then Platonism, conceptualism and nominalism as the fundamental standpoints on the question o f mathematical objects are presented. Examples are given of concrete (specific) theories w ith in these standpoints and their implications (also epistemological ones) are shown.
What do mathematicians dispute about, or on the ontological status of the objects of mathematics